To solve equations in the form \( ax - b = c \), you need to follow these steps. Here’s how to fill in the blanks for your example:
Step 1: Add \( b \) to both sides
For the equation:
\( 2x - 7 = 3 \)
You add 7 to both sides:
\( 2x - 7 + 7 = 3 + 7 \)
This simplifies to:
\( 2x = 10 \)
Step 2: Divide both sides by \( a \)
Now, divide both sides by \( 2 \) (since \( a = 2 \) in this case):
\( \frac{2x}{2} = \frac{10}{2} \)
This simplifies to:
\( x = 5 \)
So the completed steps would be:
- Add \( b \) to both sides
- Divide both sides by \( a \)
Final answer: \( x = 5 \)